2008
DOI: 10.1002/aic.11510
|View full text |Cite
|
Sign up to set email alerts
|

Solar steam reforming of natural gas for hydrogen production using molten salt heat carriers

Abstract: in Wiley InterScience (www.interscience.wiley.com).The utilization of concentrated solar energy as external heat source for methane steam reforming has been investigated. Molten salts at temperatures up to 5508C can be used as solar heat carrier and storage system, and hydrogen selective membranes can be used to drive reforming reaction at lower temperatures than conventional (\5508C), with hydrogen purification achieved thereby. The combination of new technologies such as membranes and membrane reactors, conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 35 publications
2
57
0
Order By: Relevance
“…The utilization of molten salts up to 550 • C with a heat storage system can ensure constant-rate solar heat supply even for an energy demanding industrial chemical process like the steam reforming of methane [11]. Moreover, in order to use hydrogen as an energy carrier, a transition period comprising both renewable and fossil sources will exist.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of molten salts up to 550 • C with a heat storage system can ensure constant-rate solar heat supply even for an energy demanding industrial chemical process like the steam reforming of methane [11]. Moreover, in order to use hydrogen as an energy carrier, a transition period comprising both renewable and fossil sources will exist.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum conversion achieved in these studies ranged between 15 and 21% [76,78]. Simulations concluded that increasing the residence time, steam to fuel ratio, and inlet temperature increases the methane conversion, while increasing the operating pressure decreases the methane conversion [77].…”
Section: Asterix Project [75 64]mentioning
confidence: 88%
“…Simulations concluded that increasing the residence time, steam to fuel ratio, and inlet temperature increases the methane conversion, while increasing the operating pressure decreases the methane conversion [77]. Moreover, conversion was increased to between 54 and 69% when multiple reactor stages with hydrogen permeable membranes between each reactor stage was utilized [78].…”
Section: Asterix Project [75 64]mentioning
confidence: 99%
See 2 more Smart Citations